Additive Effects of Exercise and Vitamin D Supplementation (with and without Calcium) on Bone Mineral Density in Older Adults: A Systematic Review and Meta-Analysis - Cecilie Fischer; Franz Jakob; Matthias Kohl; Stephanie Kast; Simon Von Stengel; Katharina Kerschan-Schindl; Uwe Lange; Friederike Thomasius; Stefan Peters; Michael Uder; Wolfgang Kemmler (Journal of Osteoporosis)
Exercise is a recognized component in the prevention and therapy of osteoporosis. The present systematic review and meta-analysis aimed to determine the effect of Vitamin D (Vit-D) added to exercise versus exercise alone on bone mineral density (BMD) at the lumbar spine (LS) or hip in older adults. A systematic review based on six literature databases according to PRISMA included (a) exercise trials, with an exercise (EX) and a combined exercise + Vit-D group (EX + Vit-D), (b) intervention ≥ 6 months, and (c) BMD assessments at LS or hip. Effects sizes (MD) and 95%-confidence intervals (95%-CI) were calculated using a random-effect model that includes the inverse heterogeneity model (IVhet). Five studies with 281 participants in the EX and 279 participants in the EX + Vit-D were included. No significant differences between EX versus EX + Vit-D were observed for BMD-LS (MD: 0.002, 95%-CI: −0.033 to 0.036) or BMD-hip (MD: 0.003, 95%-CI: −0.035 to 0.042). Heterogeneity between the trial results was moderate-substantial for LS (I2 = 0%) and moderate for hip-BMD (I2 = 35%). The funnel plot analysis suggests evidence for a publication/small study bias for BMD-LS and hip results. In summary, this present systematic review and meta-analysis were unable to determine significant positive interaction of exercise and Vit-D on LS- or hip-BMD. We predominately attribute this finding to (1) the less bone-specific exercise protocols of at least two of the five studies and (2) the inclusion criteria of the studies that did not consequently focus on Vit-D deficiency. This issue should be addressed in more detail by adequately powered exercise trials with promising exercise protocols and participants with Vit-D deficiency. This trial is registered with the International Prospective Register of Systematic Reviews (PROSPERO) ID: CRD42022309813.